NUTRIENTS CONTENT OF ELEPHANT GRASS (Pennisetum purpureum) SILAGE WITH DIFFERENT LEVELS OF CALLIANDRA (Calliandra calothyrsus) LEAF MEAL ADDITION - M.B., Setiawan,; Trisnadewi, A.A.A.S.; Cakra, I G.L.O. (Jurnal Peternakan Tropika; Vol 12 No 6 (2024): Vol. 12 No. 6 Year 2024; November - Desember, 2024)
Silage is a feed ingredient produced by fermentation technology to preserve and maintain the nutrient content in it. The study aimed to determine the effect of the addition of kaliandra leaf flour ( Calliandra calothyrsus ) on the nutritional content of elephant grass silage ( Pennisetum purpureum ). The research was conducted at the Sesetan Research Station, on Jalan Raya Sesetan Gang Passion Fruit and the Laboratory of Nutrition and Animal Food, Faculty of Animal Husbandry, Udayana University. The study lasted for two months, using a complete randomized design consisting of four treatments and three replicates. The treatment consisted of P1 (elephant grass 95% + 0% kaliandra leaf flour + 5% molasses), P2 (elephant grass 85% + 10% kaliandra leaf flour + 5% molasses), P3 (elephant grass 75% + 20% kaliandra leaf flour + 5% molasses), and P4 (elephant grass 65% + 30% kaliandra leaf flour + 5% molasses). The variables observed were dry matter, organic matter, ash, crude fiber, crude fat and crude protein silage. The data obtained was analyzed using fingerprints. The results of the study on the dry material variable of P4 silage got the highest value, the variable of ash content of P4 silage got the lowest value, the variable of crude fiber of P4 silage got the lowest value, and the variable of crude protein of P4 silage got the highest value. The conclusion of this study is that the nutritional content of elephant grass silage ( Pennisetum purpureum ) added to kaliandra leaf flour ( Calliandra calothyrsus ) has increased. The addition of 30% kaliandra leaf flour is the best level to produce silage nutrient content.